Intermediate general and applied science course - Miller, Christine; Collins, Danielle; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2018)
"This course package is designed as an introduction to General and Applied Science. It satisfies the learning outcomes for British Columbia ABE Intermediate General and Applied Science, which is considered an equivalent to BC Science 10. This resource includes powerpoints, class notes, and laboratory manuals for each of three three modules: Chemistry, Biology, and Physics. Throughout these modules, students explore the scientific method, take part in peer discussions, try out their problem solving skills in classroom and laboratory settings, and learn required skills and knowledge to prepare them for the Grade 11 level of science. Quizzes and mini-finals are also available to instructors upon request."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from BC Open Textbook Project homepage (viewed March 30, 2020).
Keywords: Science -- Study and teaching (Secondary) -- British Columbia; Electronic books